2020
DOI: 10.1017/s0033291720002421
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on mediators between adversity and psychosis: potential targets for treatment

Abstract: Various psychological and biological pathways have been proposed as mediators between childhood adversity (CA) and psychosis. A systematic review of the evidence in this domain is needed. Our aim is to systematically review the evidence on psychological and biological mediators between CA and psychosis across the psychosis spectrum. This review followed PRISMA guidelines. Articles published between 1979 and July 2019 were identified through a literature search in OVID (PsychINFO, Medline and Embase) and Cochra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 91 publications
(263 reference statements)
6
59
1
Order By: Relevance
“…We postulate that physical activity, in conjunction with regular treatment may reduce the physiological or subjective stress response, and potentially lessen some of the adverse longterm effects of childhood trauma in SZ and BD. Given the importance of childhood trauma in the prognosis and illness course of patients with SZ and BD (Nemeroff 2016;Teicher et al 2016;Pruessner et al 2017), evidence-based interventions addressing long-term effects of trauma experiences are needed (Alameda et al 2020). Although there was no difference in body mass index between groups in the current study, a history of childhood trauma has been associated with higher body mass index and C-reactive protein (CRP) (Aas et al 2017;Moraes et al 2017) and poorer physical health behaviour in general (Grigsby et al 2020) demonstrating the need to improve physical health in individuals with trauma experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We postulate that physical activity, in conjunction with regular treatment may reduce the physiological or subjective stress response, and potentially lessen some of the adverse longterm effects of childhood trauma in SZ and BD. Given the importance of childhood trauma in the prognosis and illness course of patients with SZ and BD (Nemeroff 2016;Teicher et al 2016;Pruessner et al 2017), evidence-based interventions addressing long-term effects of trauma experiences are needed (Alameda et al 2020). Although there was no difference in body mass index between groups in the current study, a history of childhood trauma has been associated with higher body mass index and C-reactive protein (CRP) (Aas et al 2017;Moraes et al 2017) and poorer physical health behaviour in general (Grigsby et al 2020) demonstrating the need to improve physical health in individuals with trauma experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Although childhood trauma experiences are linked to the development of more severe clinical profile in schizophrenia (SZ) and in bipolar disorder (BD), treatment studies specifically focussing on childhood trauma experiences such as, for example, Eye Movement Desensitisation Reprogramming (EMDR) or trauma focussed Cognitive Behavioural Therapy (CBT) are still sparse (Alameda et al 2020). Physical activity promotes resilience and reduces stress levels (Deuster and Silverman 2013), including reducing negative emotions following a stress task (Childs and de Wit 2014) and protects against adverse behavioural and metabolic consequences of stressful events (Silverman and Deuster 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, the long-term negative effects of childhood maltreatment on the social and cognitive functioning of psychotic patients have led to significant researches into the understanding of possible underlying psychological mechanisms [8][9][10][11][12][13]. In this regard, numerous psychological models have been proposed to explain the association between childhood maltreatment and psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, numerous psychological models have been proposed to explain the association between childhood maltreatment and psychosis. For instance, one of the most important of these models has shown that childhood maltreatment may result in psychosis via a pathway of posttraumatic stress disorder-related symptoms, including intrusive memories and dissociation [12,13]. In this conceptual model, "flash-backs could be interpreted as being externally generated, which leads to hallucinatory experiences and hampers reality testing" [12].…”
Section: Introductionmentioning
confidence: 99%
“…Alameda et al systematically reviewed 48 studies that covered approximately 85 000 individuals. 2 They determined a solid evidence for negative cognitive schemas about the self, the world and others mediating this link; dissociation and post-traumatic stress disorder symptoms also play a role, particularly with hallucinations as an outcome. There was a lack of good data for any biological mediators, although this may well be a research bias rather than evidence of absence.…”
mentioning
confidence: 99%